VARIATIONS OF MANITOL LEVEL AND CORN SYRUP AS A BASE IN NUTRASEUTICAL FORMULATION OF GUMMY CANDIES SUGAR CANE SARI MARKISA YELLOW (Passiflora edulis var. Flavicanpa) - Feris Firdaus; Fajriyanto Fajriyanto (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2013)
The yellow passion fruit (Passiflora edulis var. Jlavicarpa) is formulated into a nutraceutical product in the form of a gummy candies preparation. Furthermore, various tests of gummy candies produced were organoleptic test, weight uniformity test, and favorite level test. Based on the results of the research, yellow passion fruit (Passiflora edulis var.jlavicarpa) can be formulated into good nutraceutical products in the form of gummy candies preparations. The result of organoleptic test showed that the preparation of gummy candies formula 3 with the base of mannitol and corn syrup (25%: 75%) had the best form, color, taste, odor and texture compared to other formula. Based on the results of uniformity test weight is known that the variation in the ratio of mannitol and corn syrup as the basis of gummy candies does not affect the uniformity of weight but affects the form of gummy candies preparations. Based on the results of hedonic test of respondents for the parameters of shape, color, taste, odor, and texture of gummy candies of passion fruit essence, formula 3 is the most preferred formula by the respondents.